EU Artificial Intelligence Act : Dynamics in General-Purpose Systems - Lindbäck, Gustaf (My University, 2023)
The Artificial Intelligence Act (AI Act) proposed by the European Commission 21.4.2021 sets out EU ́s ambitious goals of regulating artificial intelligence within the Union. The proposal initiates the first attempt in the world to regulate the general field of artificial intelligence, and its impact is expected to be of fundamental importance both in the EU and globally. The AI Act uses a risk-based approach to impose extensive requirements on providers putting high-risk AI systems on the European market. Whereas the AI Act aims at ensuring future-proof regulation, to meet rapid technological progress, the Commission proposal does not regulate general-purpose AI (GPAI). These are systems that can have a wide range of application such as speech or image recognition, translation, pattern detection, audio or video generation etc. Leaving GPAI outside the scope of the Act could prove detrimental as developers of potentially harmful systems might escape the safeguards of the AI Act. This study examines whether or not the AI Act should bring GPAI within its scope, and if so, under which conditions. Two areas of particular focus are the allocation of responsibility between stakeholders in the AI value chain, and the process for conformity assessment under the AI Act. This study further examines the Brussels Effect of the AI Act and consider EU ́s responsibility as it finds itself in a first-mover advantage to regulate artificial intelligence. This study finds that widespread deployment of GPAI carries significant risk to the safety and fundamental rights of EU citizens, and thus should be regulated within the scope of the AI Act. This should be done within the Act itself, and not via an implementing act, as proposed by the Council General Approach on 6th December 2022. Furthermore, the current structure of the Act should shift focus from the intended purpose of AI to a structure around the foreseeable use of AI systems. The study finds further that the regulation of GPAI should involve all relevant stakeholders in the product cycle and that GPAI systems should be subject to a complete risk assessment involving a third party. The study also identifies risks that the AI Act might over-rely on harmonized standards for the implementation of the Act. It is contested whether assigning regulatory power to private standardization bodies in significant legal or ethical questions is appropriate.

Euroopan komission 21.4.2021 esittämä Tekoälysäädös (The AI Act) asettaa kunnianhimoisia tavoitteita säännellä tekoälyä EU:n sisällä. Ehdotus on maailman ensimmäinen yritys säännellä tekoälyn käyttöä ja sen vaikutusten odotetaan olevan merkittäviä sekä EU maille että maailmanlaajuisesti. Tekoälysäädös käyttää riskiin perustavaa lähestymistapaa asettaakseen laajoja vaatimuksia palveluntarjoajille, jotka tuovat suuririskisiä tekoälyjärjestelmiä Euroopan markkinoille. Vaikka säädöksellä pyritään varmistamaan tulevaisuuden kannalta kestävää sääntelyä ja vastata nopeaan teknologiseen kehitykseen, ehdotuksessa ei säännellä yleiskäyttöistä tekoälyä (generalpurpose AI). Näillä yleiskäyttöisillä tekoälyjärjestelmillä on monenlaisia sovelluksia, kuten kuvan tai äänen tunnistus, kielikäännös, äänen ja videon tuottaminen jne. Tämän jättäminen säädöksen soveltamisalan ulkopuolelle voisi olla haitallista, koska mahdollisest haitallisten järjestelmien kehittäjät voivat välttyä säädöksen seuraamuksilta. Tämä tutkimus tarkastelee, pitäisikö Tekoälysäädöskseen sisällyttää myös yleiskäyttöinen tekoäly sen soveltamisalaan ja siinä tapauksessa millä ehdoilla. Kaksi painopistealuetta ovat vastuunjako tekoälyn arvoketjun sidosryhmien kesken sekä Tekoälysäädöksen mukainen vaatimusmukaisuuden arviointi. Tämä tutkimus tarkastelee lisäksi myös Bryssel-efektia ja EU:n vastuuta, koska EU on etusijalla tekoälyn säätelyssä. Tässä tutkimuksessa todetaan, että yleiskäyttöisen tekoälyn laajalle levinneisyyteen liittyy merkittäviä riskejä EU-kansalaisten turvallisuudelle ja perusoikeuksille, ja siksi sitä olisi säänneltävä Tekoälysäädöksen puitteissa. Tämä tulisi tehdä itse Tekoälysäädösksesä, ei täytäntöönpanosäädöksellä, kuten neuvostossa ehdotettiin 6. joulukuuta 2022. Lisäksi Tekoälysäädöksen nykyisen rakenteen pitäisi siirtää painopistettä tekoälyn tarkoituksesta rakenteeseen, johon liittyy tekoälyjärjestelmien ennakoitavissa oleva käyttö. Tutkimuksessa todetaan lisäksi, että yleiskäyttöisien tekoälyjärjestelmien sääntelyyn olisi otettava mukaan kaikki asiaankuuluvat sidosryhmät tuotesykliin ja että yleiskäyttöisistä tekoälyjärjestelmistä olisi tehtävä täydellinen riskiarviointi, johon osallistuu kolmas osapuoli. Tutkimuksessa tunnistetaan myös riskejä siitä, että Tekoälysäädös saattaa liiaksi turvautua yhdenmukaistettuihin standardeihin säädöksen toimeenpanossa. On kyseenalaista, onko sääntelyvallan antaminen yksityisille standardointielimille merkittävissä oikeudellisissa tai eettisissä kysymyksissä ajanmukaista.
Keywords: EU Law, EU Artificial Intelligence Act, artificial intelligence, general-purpose artificial intelligence, EU-Oikeus, Tekoälysäädös, tekoäly, yleiskäyttöistä tekoälyä